The art and science of data curation: Lessons learned from constructing a virtual collection. (March 2018) - Bugbee, Kaylin; Ramachandran, Rahul; Maskey, Manil; Gatlin, Patrick
Abstract: A digital, or virtual, collection is a value added service developed by libraries that curates information and resources around a topic, theme or organization. Adoption of the virtual collection concept as an Earth science data service improves the discoverability, accessibility and usability of data both within individual data centers but also across data centers and disciplines. In this paper, we introduce a methodology for systematically and rigorously curating Earth science data and information into a cohesive virtual collection. This methodology builds on the geocuration model of searching, selecting and synthesizing Earth science data, metadata and other information into a single and useful collection. We present our experiences curating a virtual collection for one of NASA's twelve Distributed Active Archive Centers (DAACs), the Global Hydrology Resource Center (GHRC), and describe lessons learned as a result of this curation effort. We also provide recommendations and best practices for data centers and data providers who wish to curate virtual collections for the Earth sciences. Highlights: A virtual collection is a service that improves data accessibility and usability. A virtual collection use case was curated for the GHRC data center. Virtual collections must be rigorously curated to ensure trustworthiness to users. Innovative approaches to curation lower the effort required to create virtual collections.